Plant-based Food Cyanidin-3-Glucoside Modulates Human Platelet Glycoprotein VI Signaling and Inhibits Platelet Activation and Thrombus Formation. Issue 10 (30th August 2017) - Yao, Yanling; Chen, Yanqiu; Adili, Reheman; McKeown, Thomas; Chen, Pingguo; Zhu, Guangheng; Li, Dan; Ling, Wenhua; Ni, Heyu; Yang, Yan
Abstract: Background: Platelets play an important role in hemostasis, thrombosis, and atherosclerosis. Glycoprotein VI (GPVI) is a major platelet receptor that interacts with exposed collagen on injured vessel walls. Our previous studies have shown that anthocyanins (a type of natural plant pigment) attenuate platelet function; however, whether anthocyanins affect collagen-induced GPVI signaling remains unknown. Objective: The objective of this study was to explore the effects of cyanidin-3-glucoside (Cy-3-g, one of the major bioactive compounds in anthocyanins) on platelet activation and thrombosis and the GPVI signaling pathway. Methods: Platelets from healthy men and women were isolated and incubated with different concentrations (0, 0.5, 5, and 50 μM) of Cy-3-g. The expression of activated integrin αIIbβ3, P-selectin, CD63, and CD40L, fibrinogen binding to platelets, and platelet aggregation were evaluated in vitro. Platelet adhesion and aggregation in whole blood under flow conditions were assessed in collagen-coated perfusion chambers. Thrombosis and hemostasis were assessed in 3–4-wk-old male C57BL/6J mice through FeCl3 -induced intravital microscopy and tail bleeding time. The effect of Cy-3-g on collagen-induced human platelet GPVI signaling was explored with Western blot. Results: Cy-3-g attenuated platelet function in a dose-dependent manner. The 0.5-μM dose of Cy-3-g inhibited ( P < 0.05) human platelet adhesion and aggregation to collagen at both venous (−54.02%) and arterial (−22.90%) shear stresses. The 5-μM dose inhibited ( P < 0.05) collagen-induced human platelet activation (PAC-1: −48.21%, P-selectin: −50.63%), secretion (CD63: −73.89%, CD40L: −43.70%), fibrinogen binding (−56.79%), and aggregation (−17.81%). The 5-μM dose attenuated ( P < 0.01) thrombus growth (−66.67%) without prolonging bleeding time in mice. The 50-μM dose downregulated ( P < 0.05) collagen-induced GPVI signaling in human platelets and significantly decreased phosphorylation of Syk–linker for activation of T cells (LAT)–SLP76 (Syk: −39.08%, LAT: −32.25%, SLP76: −40.00%) and the expression of Lyn (−31.89%), Fyn (−36.27%), and phospholipase C-γ2 (−39.08%). Conclusions: Cy-3-g inhibits human platelet activation, aggregation, secretion, and thrombus formation, and downregulates the collagen-GPVI signaling pathway. Supplementation of Cy-3-g may have protective effects against atherothrombosis.